The Effect of TikTok Use Intensity on Moral Disengagement of Senior High School Students with Self Control as Mediator Variable - Yudha, Trigasi Carina Ayu; Matulessy, Andik; Rini, Amanda Pasca (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The purpose of this study is to ascertain how self-control, as a mediator, affects the degree of TikTok use and moral disengagement. Quantitative research methodologies are used in this work. Surabaya City high school students made up the study's population. Nonprobability sampling combined with incidental sampling is the method of sampling that is employed. A scale was employed in the data gathering method. The traditional assumption test and path analysis are the methods of analysis employed. The results showed that the self-control variable was unable to mediate the effect of the intensity of using tiktok on moral disengagement, self-control with moral disengagement did not have a significant relationship, the intensity of using tiktok with moral disengagement had a significant relationship, and the intensity of using tiktok with self-control had a significant relationship. The results of this study are expected to contribute to the development of educational psychology, especially theories regarding moral behavior and self-control in a digital context.